A Inversão das distâncias: do som do corpo ao corpo do som - Menezes, Flo [UNESP] (Univ Federal Goias, 2014)
This essay deals with the relationship between the body of the composer and his sounds, approaching - by a philosophical point of view - the process of objectivation of sound along the history of musical writing (escritura = musical scripture), until coming up the emergence of electroacoustic music. At this point, the text handles with the dialectic between analogical and digital resources and with the most crucial problems of electroacoustic music in our days.

Este ensaio discorre sobre a relação entre o corpo do compositor e seus sons, abordando, por um viés filosófico, o processo de objetivação do som no decurso da história da escritura musical, até desaguar no advento das poéticas eletroacústicas. Lá chegando, o texto discorre sobre a dialética entre recursos analógicos e digitais e sobre os problemas mais pungentes da composição eletroacústica nos dias de hoje.
The Inversion of the Distances - from the Sound of the Body to the Body of Sound
Keywords: Musical composition; Electroacoustic poetics; Philosophy of music; Composição musical; Poética eletroacústica; Filosofia da música